2019
DOI: 10.3390/ani9100742
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance of Broiler Chicks Ingesting Dietary Betaine and/or Creatine

Abstract: Simple SummaryImproving broiler performance is still an essential task in animal production, especially under certain environmental challenge conditions. Heat stress is among the first and crucial limiting factors of the development of poultry production in warm regions. Betaine (B) and creatine (C) are seemingly two promising additives that showed enhancement in water metabolism in several animal species. Despite the clear beneficial effect of B and/or C on water metabolism, limited information is available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It has been reported that increasing the level of carnitine [ 54 ] and creatine [ 55 ] in muscles [ 53 ] and creatinine in blood [ 56 ] depends on the capacity of betaine as a methyl donor. Dietary betaine and/or creatine have indicated significant efficacy in enhancing the water holding capacity, and consequently, efficient nutritional hyper-hydration process, thereby reducing the risk of broiler chicks exposed to high ambient temperature [ 57 ]. A recent study indicated that adding guanidino acetic acid and betaine to broiler ducks’ diets boosted their levels of creatine and ATP level in pectoral muscle as well as creatine kinase in the blood plasma, but reduced the activities of lactatedehydrogenase and L-arginine: glycine amidino transferase enzymes [ 58 ].…”
Section: Interaction Of Betaine With Other Elementsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that increasing the level of carnitine [ 54 ] and creatine [ 55 ] in muscles [ 53 ] and creatinine in blood [ 56 ] depends on the capacity of betaine as a methyl donor. Dietary betaine and/or creatine have indicated significant efficacy in enhancing the water holding capacity, and consequently, efficient nutritional hyper-hydration process, thereby reducing the risk of broiler chicks exposed to high ambient temperature [ 57 ]. A recent study indicated that adding guanidino acetic acid and betaine to broiler ducks’ diets boosted their levels of creatine and ATP level in pectoral muscle as well as creatine kinase in the blood plasma, but reduced the activities of lactatedehydrogenase and L-arginine: glycine amidino transferase enzymes [ 58 ].…”
Section: Interaction Of Betaine With Other Elementsmentioning
confidence: 99%
“…Broiler chickens that received dietary 0.05%, 0.05–0.10%, and 0.28% betaine showed no improvement in parameters of performance [ 10 , 79 ]. Dietary betaine and/or creatine supplementation during the rearing period of broiler chickens did not affect production parameters [ 57 ].…”
Section: Different Beneficial Effects Of Dietary Betaine In the Poult...mentioning
confidence: 99%
See 3 more Smart Citations